Recent advancements in nanotechnology-based bacteriophage delivery strategies against bacterial ocular infections - Patil R.; Dehari D.; Chaudhuri A.; Kumar D.N.; Kumar D.; Singh S.; Nath G.; Agrawal A.K. (My University, 2025)
Antibiotic resistance is growing as a critical challenge in a variety of disease conditions including ocular infections leading to disastrous effects on the human eyes. Staphylococcus aureus (S. aureus) mediated ocular infections are very common affecting different parts of the eye viz. vitreous chamber, conjunctiva, cornea, anterior and posterior chambers, tear duct, and eyelids. Blepharitis, dacryocystitis, conjunctivitis, keratitis, endophthalmitis, and orbital cellulitis are some of the commonly known ocular infections caused by S. aureus. Some of these infections are so fatal that they could cause bilateral blindness like panophthalmitis and orbital cellulitis, which is caused by methicillin-resistant S. aureus (MRSA) and vancomycin-resistance S. aureus (VRSA). The treatment of S. aureus infections with known antibiotics is becoming gradually difficult because of the development of resistance against multiple antibiotics. Apart from the different combinations and formulation strategies, bacteriophage therapy is growing as an effective alternative to treat such infections. Although the superiority of bacteriophage therapy is well established, yet physical factors (high temperatures, acidic pH, UV-rays, and ionic strength) and pharmaceutical barriers (poor stability, low in-vivo retention, controlled and targeted delivery, immune system neutralization, etc.) have the greatest influence on the viability of phage virions (also phage proteins). A variety of Nanotechnology based formulations such as polymeric nanoparticles, liposomes, dendrimers, nanoemulsions, and nanofibres have been recently reported to overcome the above-mentioned obstacles. In this review, we have compiled all these recent reports and discussed bacteriophage-based nanoformulations techniques for the successful treatment of ocular infections caused by multidrug-resistant S. aureus and other bacteria. © 2023 Elsevier GmbH